The value of oral appliances in the treatment of obstructive sleep apnoea - Rose, Edmund Clemens (German Medical Science, 2006)
Oral appliances have long been used to treat snoring and mild to moderate obstructive sleep apnoea. This kind of treatment is considered an alternative, non-invasive treatment option. Mandibular protrusive appliances enlarge and stabilise the oro- and hypo-pharyngeal airway space by advancing the mandible, and stretching the attached soft tissue, in particular the tongue, soft palate, uvula, and the pharyngeal tissues. This article summarises the indications, contraindications, and possible side-effects of using oral appliances. Therapeutic efficacy is influenced by multiple parameters that are clinically difficult to control. One major parameter is the patient`s stomatognathic situation of the patient. Thus oral appliances are restricted to patients whose dental retention is adequate for permanent treatment and who do not suffer from temporomandibular joint dysfunction. Regular follow-up sleep studies and dental evaluations are necessary to ensure adequate permanent treatment.